Does the development of ran depend on the age of the beginning of reading learning process? - Roberta Ceccato; Lorena Caballero-Gascón; Olga Fernandez-García; Isabel Chaves; María Dolores Gil- Llario (INFAD, 2018)
Background: The ability of the student to quickly name familiar stimuli (RAN) is a factor involved in reading performance that can be evaluated indiscriminately throughout the first years of schooling. The objectiveof this study, then, is to analyze if the acquisition of this ability depends on variables related to an early initiation to the reading-writing or if its development is related to factors of chronological maturity. Method: To this end, the RAN test was applied to 71 6-7 years old children from Croatia (culture in which the initiation to reading is later); to 44 4-5 years old Spanish children (equating the two groups by age of beginning of the reading-writing) and to 43 6-7 years old Spanish children (equating the two groups by chronological age). The results show that by comparing the group of Croatian children with the group of Spanish children aged 4-5 years, significant differences stand out in the appointment times of the stimuli of the 4 different components of the test. Older children recognize numbers and letters more quickly while younger ones take longer in these stimuli, recognizing objects and colors more quickly. However, comparing the two groups of children aged 6-7 years (Croatians and Spanish), no statistically significant differences were found. It is concluded that the development of the RAN is characterized by an earlier acquisition of nonsymbolic stimuli (objects-colors) than symbolic stimuli (letters-numbers) and that this acquisition is related more to factors of chronological maturity than of age of beginning of the reading-writing. This ability, therefore, despite being closely related to the learning of reading and writing, seems to develop independently of the age at which such learning begins.